Confirmatory factor analysis of the German Readiness for Interprofessional Learning Scale (RIPLS-D) - Mahler, Cornelia; Giesler, Marianne; Stock, Christian; Krisam, Johannes; Karstens, Sven; Szecsenyi, Joachim; Krug, Katja (Journal of interprofessional care, 2016)
Over the past five years, the development of interprofessional education programmes has been gaining momentum in Germany fostering the need to evaluate these with appropriate instruments. Instead of developing a new instrument for evaluation purposes, the Readiness for Interprofessional Learning Scale (RIPLS) was chosen, as it is a widespread instrument that has been used in a variety of different educational settings and countries. The German version of the RIPLS was administered in two sites to health professional students in Heidelberg and Freiburg, Germany. Cronbach’s alpha was used to examine internal consistency. Confirmatory factor analysis (CFA) was performed for confirmation of the underlying factor structure of the RIPLS-D. In total, 531 questionnaires were analysed. The instrument showed overall reliability (0.81) and low reliability (< 0.7) in the subscales. The underlying factor structure could not be confirmed. These results contribute further evidence on deficits with the RIPLS. Despite known issues, the RIPLS continues to be translated and applied. This paper highlights the problematic issues in the RIPLS-D and does not recommend its use.